2020
DOI: 10.3389/fimmu.2020.00813
|View full text |Cite
|
Sign up to set email alerts
|

NK Cell Development in Times of Innate Lymphoid Cell Diversity

Abstract: After being described in the 1970s as cytotoxic cells that do not require MHC-dependent pre-activation, natural killer (NK) cells remained the sole member of innate lymphocytes for decades until lymphoid tissue-inducer cells in the 1990s and helper-like innate lymphoid lineages from 2008 onward completed the picture of innate lymphoid cell (ILC) diversity. Since some of the ILC members, such as ILC1s and CCR6 − ILC3s, share specific markers previously used to identify NK cells, these findings provoked the ques… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 270 publications
(489 reference statements)
1
38
0
Order By: Relevance
“…Recently, NK cells were classified in the family of innate lymphoid cells (ILCs), which gather cytotoxic effectors (NK cells) and helper-type ILCs (h-ILCs) [ 20 ]. The h-ILCs arise from a common lymphoid progenitor [ 21 , 22 ] and are located in mucosal barriers and various tissues [ 23 ], including the intestine, skin, lung, and adipose tissue [ 24 ]. ILCs are heterogeneous subsets of lymphocytes that have emerging roles in orchestrating immune response and contribute to maintaining homeostasis and regulating tissue inflammation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, NK cells were classified in the family of innate lymphoid cells (ILCs), which gather cytotoxic effectors (NK cells) and helper-type ILCs (h-ILCs) [ 20 ]. The h-ILCs arise from a common lymphoid progenitor [ 21 , 22 ] and are located in mucosal barriers and various tissues [ 23 ], including the intestine, skin, lung, and adipose tissue [ 24 ]. ILCs are heterogeneous subsets of lymphocytes that have emerging roles in orchestrating immune response and contribute to maintaining homeostasis and regulating tissue inflammation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…ILCs in Group 3 use RORC to produce IL-17 and IL-22 (TH17-related cytokines) [14][15][16][17]. Hematopoietic stem cells (HSCs) give rise to all the different blood cell progenitors, among which common lymphoid progenitors (CLPs) are precursors of all the ILC subtypes as well as B cells and T cells [18,19]. Recently, an early ILC progenitor, also known as the common innate lymphoid progenitor (CILP), was identified as CXCR6+ cells within the aLP population [20].…”
Section: Development and Differentiation Of Ilc Lineagesmentioning
confidence: 99%
“…In addition, lymphoid tissue inducer (LTi) cells as well as CD4+ T-cells can be derived directly from CHILP [6]. Cells with a high level of PLZF (promyelocytic leukemia zinc finger protein) and a4b7/Lin-/IL-7Ra+/cKit+ and CXCR6-are defined as the innate lymphoid cell progenitor (ILCP) population that originates from the CHILP [19]. Recently it has been shown that both cytotoxic and helper ILCs can be derived from RORgt+ ILCPs [23].…”
Section: Development and Differentiation Of Ilc Lineagesmentioning
confidence: 99%
“…The NK cell component of this system is comprised of about 2 to 18% of the lymphocytes in peripheral blood (Vivier et al, 2008 as members of the innate lymphoid cell (ILC) family, that are primarily characterized by their ability to kill target cells. (Stokic-Trtica et al, 2020). This cytotoxic activity is regulated by the "missing self" postulate (Ljunggren & Kärre, 1990).…”
Section: Nk Cell Definitionmentioning
confidence: 99%